Cycling and sustainability - Parkin, John, 1946- (Emerald, 2012)
This title explores the reasons for difficulties in making cycling mainstream in many cultures, despite its claims for being one of the most sustainable forms of transport.
Includes index.
Keywords: Bicycle commuting.; Cycling -- Social aspects.; Bicycle lanes.; elektronické knihy; electronic books